Pengaruh Perbandingan Terigu dan Tepung Sukun (Artocarpus altilis) Terhadap Karakteristik Kue Cubit - Ollyvetty Meilani, Era; Kencana Putra, I Nengah; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This study aimed to determine the effect of wheat flour and breadfruit flour ratio on the characteristics of cubit cake and to know the best ratio of wheat flour and breadfruit flour to produce cubit cake with the best characteristics. The experimental design used in this research was a Completely Randomized Design (CRD) and a Randomized Block Design (RBD) with a ratio of wheat flour and breadfruit flour as a treatment that consisting of 6 levels, namely 100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40%, 50%:50%. The treatment was repeated 3 times to obtained 18 units of the experiment. The data were analyzed by Analysis of Variance (ANOVA) and if the treatment had a significant effect on the variable then continued with Duncan Multiple Range Test (DMRT). The result showed that the ratio of wheat flour and breadfruit flour had a very significant effect on the content of moisture, ash, protein, fat, carbohydrate, crude fiber, strength of expand, criteria hedonic of colour, texture, taste, and overall acceptance and criteria skor of texture, taste, and aroma. Ratio of 70% wheat flour and 30% breadfruit flour produced a cubit cake with the best characteristics with 35.09% water content, 1.61% ash, 6.08% protein, 24.99% fat, 32.22% carbohydrate, 2.18% crude fiber, 17.72% strength of expand, slightly soft texture, taste and aroma rather typical of breadfruit, colour and overall acceptance were liked.